VITAMIN D IMPACT ON HUMAN HEALTH AND ITS RELATION WITH SEVERAL DISEASES - Al-shahwan, Moayad; Gacem, Sabrina Ait; Shamseddin, Shahd; Sammour, Marwa (International Journal of Applied Pharmaceutics, 2018)
Vitamins are organic nutrients and substances that are needed for many biochemical functions. They are one of the six essential elements required for human life. Vitamin D is also known among the public as the Sunshine vitamin, as it is produced internally within the human body when exposed to sunlight and it is well known that the big majority of United Arab Emirates (UAE) population suffer from its deficiency. They are usually not found inside the body and therefore must be eaten from food or taken by supplements. Vitamin D that is obtained from diet or body synthesis when it is exposed to sufficient sunlight is biologically inactive without the enzymatic activation that converts it into its active form in the liver and kidney. Deficiency of vitamin D could lead to many troubling diseases such as depression including seasonal affective disorder, Parkinson's disease, Alzheimer's disease, Arthritis (gout, osteoarthritis, tendonitis), Osteoporosis, gum and teeth diseases, obesity, diabetes, heart diseases, metabolic syndromes, immunity related diseases (sclerosis, erythematosis), and cancer, which will be discussed in this review. The main objective of the current review is to evaluate the associations of vitamin D with the diverse health outcomes according to the latest studies done so far.